Chemical glycomics enrichment: imaging the recycling of sialic acid in living cells. Issue 3 (2nd January 2018) - Gilormini, Pierre André; Lion, Cédric; Vicogne, Dorothée; Guérardel, Yann; Foulquier, François; Biot, Christophe
Abstract: The development of metabolic oligosaccharide engineering (MOE) over the past two decades enabled the bioimaging studies of glycosylation processes in physio‐pathological contexts. Herein, we successfully applied the chemical reporter strategy to image the fate of sialylated glycoconjugates in healthy and sialin‐deficient patient fibroblasts. This chemical glycomics enrichment is a powerful tool for tracking sialylated glycoconjugates and probing lysosomal recycling capacities. Thus, such strategies appear fundamental for the characterization of lysosomal storage diseases.